Réflexions sur la situation actuelle de l’assurance et ses conséquences - Chouinard, Pierre (Assurances, 1986)
In the following text, the author discusses the situation currently prevailing in the insurance industry by first exposing its weaknesses and then giving the key elements of the solution: computerization, in depth study of risks and rates required. In sum, the author presents the logical structure of an industry requiring timely solutions and not merely the intervention of interested parties (insurers, intermediaries and insureds) at the time of serious crisis.